1979
DOI: 10.1128/aem.37.2.339-342.1979
|View full text |Cite
|
Sign up to set email alerts
|

Association of Actinomycete-Like Bacteria with Soil-Feeding Termites (Termitidae, Termitinae)

Abstract: Electron microscopy of the hindgut showed that actinomycete-like bacteria were the principal microbial associates of two African species of soil-feeding termites. Elongated cuticular spines provided attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…A specific ecological niche where actinomycetes may have a role in lignocellulose degradation is as symbionts in the gut of higher termites. Direct observation of filamentous microorganisms in situ suggested that actinomycetes were not simply transitory but had formed a stable association [59]. More recently, cellulolytic actinomycetes have been isolated from the hindgut of four different termites [27].…”
Section: Ecological Rolementioning
confidence: 99%
“…A specific ecological niche where actinomycetes may have a role in lignocellulose degradation is as symbionts in the gut of higher termites. Direct observation of filamentous microorganisms in situ suggested that actinomycetes were not simply transitory but had formed a stable association [59]. More recently, cellulolytic actinomycetes have been isolated from the hindgut of four different termites [27].…”
Section: Ecological Rolementioning
confidence: 99%
“…Termite guts contained actinomycetes species similar to those in the microfloral layers of general soil profile. This might be because of the C. lacteus' ability to use soil to construct large mounds in the eastern and south eastern parts of Australia (Hill 1942) and actinomycetes might be part of soil feeding termite nourishment as they constitute significant component of soil organic matter rather than having gut specific occurrence with functional roles (Bignell et al 1979;Anklin-Muhlemann et al 1995). However, detection of phage resistant actinomycetes which grew despite the polyvalent phage treatment (Figs 1-3 Figure 4 Phylogenetic tree of 16S rRNA gene sequences obtained from termite gut associated Microbispora species (USC-360), compared against sequences obtained from public databases.…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous prokaryotic organisms, putatively actinobacteria, have been frequently described in termite guts since the detection of Micromonospora species by Hungate (1946) and Sebald and Prévot (1962). Bignell and co-workers since the late 1970s cultured large numbers of streptomycetes (Bignell et al 1979) followed by other successful culturing attempts for Arthrobacter, Aureobacterium, Cellulosimicrobium, Cellulomonas, Kocuria, Microbacterium, Micrococcus, Rhodococcus and Nocardia species (Kuhnigk et al 1994;Schäfer et al 1996;Kuhnigk and König 1997;Bakalidou et al 2002;Wenzel et al 2002). Although microscopical evidence suggests that actinobacterial clusters are not simply accidental occupants of the intestinal lumen, but intimately associated with the absorptive epithelia (König and Varma 2006;; still information on these organisms in culture is incomplete.…”
mentioning
confidence: 99%
“…Two kinds of organism predominate: slender filaments of finite length, putatively spirochaetes, immediately adjacent to the epithelium and larger filaments of indeterminate length which are most abundant at a greater distance from the epithelium. The latter group in some cases form a sheath around the food bolus, occupying part of the ectoperitrophic space; their precise affiliation is unknown but we have argued elsewhere that they may be classified as actinomycetes (Bignell, Oskarsson & Anderson, 1979;1980b). Thus in contrast to some previous suggestions (e.g.…”
Section: Associated Microorganismsmentioning
confidence: 96%